2009
DOI: 10.1136/emj.2008.061572
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Valsalva manoeuvre in the prehospital setting: a review of the literature

Abstract: This review has shown that a standard of performance of the VM technique is defined within the medical literature, but no evidence exists to determine its efficacy or use in the prehospital setting. A prehospital study is therefore required to affirm the VM as part of prehospital clinical practice guidelines for SVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 19 publications
0
22
0
1
Order By: Relevance
“…3,4 The Valsalva maneuver is a safe and recommended first line treatment for SVT, but with cardioversion rates to sinus rhythm of less than 20%. [5][6][7][8] Patients who have remained in SVT after Valsalva are most often treated with adenosine, which is commonly associated with adverse and frightening effects for patients and requires IV access. 9 Modifications to the standard Valsalva that increase relaxation phase venous return and vagal stimulation may improve cardioversion effectiveness but have not yet been tested in controlled trials.…”
Section: Objectivementioning
confidence: 99%
“…3,4 The Valsalva maneuver is a safe and recommended first line treatment for SVT, but with cardioversion rates to sinus rhythm of less than 20%. [5][6][7][8] Patients who have remained in SVT after Valsalva are most often treated with adenosine, which is commonly associated with adverse and frightening effects for patients and requires IV access. 9 Modifications to the standard Valsalva that increase relaxation phase venous return and vagal stimulation may improve cardioversion effectiveness but have not yet been tested in controlled trials.…”
Section: Objectivementioning
confidence: 99%
“…One of the many applications of the VM is its use for arresting episodes of SVT based on the relatively sudden reduction of heart rate in response to the increased venous return and arterial pressure rise following the Valsalva strain 1 2. The VM provides better results than other vagal manoeuvres (such as the carotid sinus massage or facial immersion),1 and hence it is usually recommended as a first-line, non-invasive treatment of SVT.…”
Section: Contextmentioning
confidence: 99%
“…The VM provides better results than other vagal manoeuvres (such as the carotid sinus massage or facial immersion),1 and hence it is usually recommended as a first-line, non-invasive treatment of SVT. However, some studies have shown that the standard VM rarely leads to a successful cardioversion (<20%) 3 4.…”
Section: Contextmentioning
confidence: 99%
“…GPs and internists, however, in a significant proportion (22%) would skip vagal maneuvers and would administer an antiarrhythmic agent for SVT termination. It has been reported that only a few doctors instruct their patients to perform correctly the valsalva maneuver [5,6]. In case vagal maneuvers fail to restore sinus rhythm, an antiarrhythmic agent should be administered.…”
Section: Acute Management Of Supraventricular Tachycardiamentioning
confidence: 99%